2016
DOI: 10.1111/tbed.12589
|View full text |Cite
|
Sign up to set email alerts
|

Dual Infection with Bluetongue Virus Serotypes and First-Time Isolation of Serotype 5 in India

Abstract: Summary Bluetongue is endemic in India and has been reported from most Indian states. Of late, the clinical disease is most frequently seen in the states of Andhra Pradesh, Telangana (erstwhile Andhra Pradesh state), Tamil Nadu and Karnataka. Our analysis of diagnostic samples from bluetongue outbreaks during 2010–2011 from the state of Karnataka identified bluetongue virus (BTV) serotype 5 (BTV‐5) for the first time in India. One of the diagnostic samples (CH1) and subsequent virus isolate (IND2010/02) contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…) and India (Hemadri et al . ) and the close genetic relationship of these isolates with BTV‐5 AUS, suggested a possible Eastern Asia origin for this virus. This route of entry into Australia was corroborated by the identification of BTV‐5 AUS Seg‐3 as a Malaysia A genotype (Pritchard et al .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…) and India (Hemadri et al . ) and the close genetic relationship of these isolates with BTV‐5 AUS, suggested a possible Eastern Asia origin for this virus. This route of entry into Australia was corroborated by the identification of BTV‐5 AUS Seg‐3 as a Malaysia A genotype (Pritchard et al .…”
Section: Discussionmentioning
confidence: 86%
“…There are relatively few documented accounts of BTV-5 isolations worldwide (Table S2) and only one account linking this serotype to a limited disease outbreak in Israel (Brenner et al 2010). The very recent first isolation of BTV-5 in China (Yang et al 2017) and India (Hemadri et al 2017) and the close genetic relationship of these isolates with BTV-5 AUS, suggested a possible Eastern Asia origin for this virus. This route of entry into Australia was corroborated by the identification of BTV-5 AUS Seg-3 as a Malaysia A genotype ).…”
Section: Discussionmentioning
confidence: 99%
“… 2016 ; Hemadri et al. 2017 ). In several states of India, BTV antibodies were detected in goat, cattle, camel, buffalo and mithun; however, clinical disease was not frequently reported in these species (Joardar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, serotype-specific RT-qPCR is performed to determine the dominant serotype (to infer clinical significance) rather than screen samples for all possible serotypes. Although infections with multiple serotypes have been identified in field samples [ 39 , 40 , 41 ], these may be underreported when using singleplex RT-qPCR detection strategies where samples may only be tested for a limited number of serotypes. Infection of ruminants with multiple BTV serotypes can lead to the emergence of novel, possibly more virulent, BTV strains [ 42 ].…”
Section: Discussionmentioning
confidence: 99%